Bogligt undertøj. Lidt om danske bogforsatser ca. 1880-1920 - Ilsøe, Harald (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
Harald Ilsøe: The ‘Underwear’ of a Book. About Danish Endpapers c. 1880–1920 The endpaper, i.e. the paper that connects the book block to its cover, is as rare research object of book historians, as if it were a private detail of the book, hidden from public eyes – or, humourously, the ‘underwear’ of a book. None the less, bookbinders have since the 1880’s given the endpaper growing attention and hence it has become a vital part of the decoration of a book. In this article the author presents some samples of coloured or even artistically designed Danish endpapers from the period mentioned.